Znaczenie słowa i zasada wewnętrznej motywacji cech semantycznych - Tokarski, Ryszard (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2013)
The meaning of a word has a layered structure with the clearly distinguished center (prototype, lexical meaning) and – the further towards the peripheries – with semantic connotations more and more weak-established in the system. Giving-up ofthe purely structuralist understanding of connotations (verified by semantic and morphological derivatives, collocations, repeatable lexical oppositions, or various tests) has created a danger that semantically irrelevant components may be recognized as relevant qualities. The article proposes a rule for verification of weak connotations. Underlying the principle of internal motivation of qualities is the conviction that the meaning of a word is internally structured, while each quality, especially weak connotations, are motivated by the overall structure of meaning and are explained in the context of this structure.